Activated carbon filled in a microporous titanium-foam air diffusion electrode for boosting H2O2 accumulation. (April 2023) - Deng, Fengxia; Yang, Shilin; Jing, Baojian; Qiu, Shan
Abstract: In the electro-Fenton process, there still suffers concern of low H2 O2 generation caused by inadequate mass transfer of oxygen and low selectivity of oxygen reduction reaction (ORR). To solve it, in this study, various particle sizes (850 μm, 150 μm, and 75 μm) of granular activated carbon filled in a microporous titanium-foam substate was used to develop a gas diffusion electrode (AC@Ti–F GDE). This facile-prepared cathode has seen a 176.15% improvement in H2 O2 formation compared to the conventional one. Aside from a much higher oxygen mass transfer by creating gas-liquid-solid three-phase interfaces coupled with much high dissolved oxygen, the filled AC played a significant role in H2 O2 accumulation. Among these particle sizes of AC, the one in 850 μm has observed the highest H2 O2 accumulation, reaching 1487 μM in 2 h electrolysis. Because there is a balance between chemical nature for H2 O2 formation and micropore-dominant porous structure for H2 O2 decomposition, resulting in an electron transfer of 2.12 and H2 O2 selectivity of 96.79% during ORR. In a word, the facial AC@Ti–F GDE configuration is promising for H2 O2 accumulation. Graphical abstract: Image 1 Highlights: Titanium-based air diffusion cathode was designed by filling in activated carbon. This facile-prepared cathode has seen a 176.15% improvement in H2 O2 formation. H2 O2 accumulation was a balance between porous structure and chemical nature. Filled activated carbon with 850 μm has an electron transfer of 2.12 during ORR.